2018
DOI: 10.1097/pec.0000000000001431
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and Investigation of Pediatric Bone and Joint Infections in the Pediatric Emergency Department

Abstract: Objective The objective of this study was to evaluate the presenting features of bone and joint infections with a view to identify distinguishing trends that will be useful for pediatric emergency departments. Methods We performed a retrospective review of patient records over a 12-year period in the pediatric emergency department of a large regional pediatric teaching center serving a diverse population. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 10 publications
6
29
0
Order By: Relevance
“…Pathogen isolation by culture is the key for targeted antibiotic therapy. Most of the bacteria isolated in this study were S. aureus, which is consistent with the results of other studies [3,6,[8][9] . The incidence of MRSA in our study was as high as 43.4%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Pathogen isolation by culture is the key for targeted antibiotic therapy. Most of the bacteria isolated in this study were S. aureus, which is consistent with the results of other studies [3,6,[8][9] . The incidence of MRSA in our study was as high as 43.4%.…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of MRSA in our study was as high as 43.4%. While this value is consistent with the national resistance rate of 36.1% for Staphylococcus to methicillin in Chinese children [10] , it is signi cantly higher than that reported in other countries [5,9,[11][12] , which suggests that S. aureus is seriously drug resistant in Chinese children. It is generally believed that a long time is required for the antibiotics to reach bone tissues and to achieve effective bactericidal concentrations [13] ; therefore, short-term administration of antibiotics is thought to have little effect on bacterial culture results of bone tissue specimens [14] .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the same study, MRSA isolates represented 6% of all cases caused by CA-SA [ 29 ]. Nationwide studies conducted in Spain and the UK observed rates of CA-MRSA ranging from 2.5% to 3% of all community-acquired staphylococcal infections, while PVL-SA has been isolated in 10% of these cases in Italy [ 20 , 30 ]. CA-MRSA seems to be less prevalent in European populations than in the USA, where its prevalence reached 30% in some regions within the last two decades [ 31 ].…”
Section: Aetiology and Pathogenesismentioning
confidence: 99%
“…CRP and ESR are of value in dictating the duration of therapy as well as the transition of intravenous to oral antibiotic therapy [ 29 ]. Elevated ESR, white blood cell count, and CRP have been shown to have a sensitivity of 98% in diagnosing acute OSI [ 30 ]. Magnetic resonance imaging (MRI) with gadolinium is recommended as the imaging diagnostic method of choice, and is particularly useful in the diagnosis of early osteomyelitis [ 6 , 29 ].…”
Section: Diagnosismentioning
confidence: 99%